PENGARUH PENDAPATAN, LABA DAN ARUS KAS TERHADAP NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN SEKTOR MINYAK DAN GAS BUMI YANG TERDAFTAR DI BURSA EFEK INDONESIA) - Arif, Muhammad Syaiful; Putri, Lodia Dwika; Onasis, Dini (Jurnal Akuntansi Kompetif, 2024)
This research assesses how revenue, profits, and cash flows affect the valuation oil and gas firms that listed on the Indonesia Stock Exchange. This study utilizes a quantitative descriptive methodology. The research utilized purposive sampling as the methodology. Research data collection technique include literature review and documentation. The data in this study is analyzed using multiple linear regression. The firm sample was created by conducting research on ten oil and gas firms listed on the Indonesian Stock Exchange between 2019 and 2023. Hypothesis testing results show that sales, profit, and cash flow have no meaningful effect on the valuation of oil and gas Firms listed on the Indonesian Stock Exchange. Keywords: Revenue, Profit, Cash Flow, and Company Value